Introducing numbers to 4-5 year olds at Negeri Pembina Kindergarten using number cards - Putri, Liany; Wahyuningsih, Tri; Putri, Ayu Aprilia Pangestu (Universitas Islam Malang, 2025)
Learning to mathematical concepts is crucial to mathematics. Children need to understand the meaning and concept of numbers rather than just remembering them. Facilitated by flashcard media. This research aims to the success of the flash card method for recognizing numbers. The research being conducted uses qualitative methods. Particular case analysis. The participants in the research project consisted of teachers and pupils in grade A1 at TK Negeri Pembina, East Kutai Regency. The focus of the study was the utilization of numerical card media. The methods of data collecting included observation, interviews, and documentation. Executed in the context of educational interactions between the instructor and the child research participants. The data analysis method used was data reduction implemented in the classroom during the learning process, which was then concluded. The results of the research indicated that teachers incorporated numbers beyond simply using number cards. Number recognition takes place over stages: identifying numerical symbols, understanding numerical concepts, articulating numbers 1 to 10, sequencing numbers 1 to 10, and representing numbers according to their symbols. Presented media constitutes a hindrance to learning. Organizing conflict among children and promoting inconsistency. The diversity of number cards is equally curious. Children don't feel bored when using them. The research concludes that media significantly improves children's understanding. They are easily recognizable through material things. The process of learning also becomes enjoyable.